Efficacy of nucleoside analogues for hepatitis B virus-related liver failure: A network meta-analysis - Wu Jian; Yin Fang; Zhou Xinmin (Acta Pharmaceutica)
The purpose of this study was to compare the efficacy of nucleoside analogues (NAs) in the treatment of HBV-related liver failure. The data of patients with HBV-related liver failure treated with nucleoside analogues were used to conduct a network meta-analysis. A total of 1660 patients from 12 articles about the efficacy of lamivudine, entecavir, telbivudine and tenofovir for HBV-related liver failure treatment were recruited in the study. The highest two- and three-month survival rate was recorded for patients using tenofovir. The end-stage liver disease (MELD) score and mortality in patients undergoing tenofovir treatment were the lowest. Patients treated with telbivudine had the highest one-month survival rate. Patients receiving enticavir therapy showed the lowest HBV DNA level. Our results indicate that tenofovir may be the best therapy for the treatment of HBV-related liver failure compared to other nucleoside analogues (including lamivudine, entecavir and telbivudine) and non-NAs treatment.